2023
DOI: 10.1038/s41598-023-36043-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of trans fat diet intake on metabolic parameters and pancreatic tissue in offspring of prenatal bisphenol A exposed rats

Abstract: Bisphenol A (BPA) is a plasticiser used in the manufacturing of many products and its effects on human health remain controversial. Up till now, BPA involvement in metabolic syndrome risk and development is still not fully understood. In this study, we aimed to investigate the effect of prenatal BPA exposure with postnatal trans-fat diet intake on metabolic parameters and pancreatic tissue histology. Eighteen pregnant rats were divided into control (CTL), vehicle tween 80 (VHC), and BPA (5 mg/kg/day) from gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…This explained why the maximum distance between OTUs was 0.5 ( Fig 6b ), which meant that half of the bacterial families were dissimilar to each other, which agreed with the UPGMA cluster tree of the unweighted UniFrac distance finding. Importantly, our results align with our previous findings, which showed that offspring on TFD were significantly heavier than their ND counterparts [ 41 ], which is consistent with previous research in obese humans and mice [ 36 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This explained why the maximum distance between OTUs was 0.5 ( Fig 6b ), which meant that half of the bacterial families were dissimilar to each other, which agreed with the UPGMA cluster tree of the unweighted UniFrac distance finding. Importantly, our results align with our previous findings, which showed that offspring on TFD were significantly heavier than their ND counterparts [ 41 ], which is consistent with previous research in obese humans and mice [ 36 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Rat offspring were prenatally exposed to either 5mg/kg/day BPA, a vehicle control consisting of Tween-80 (P80) or unspiked control (CTL) drinking water as described in our previous study [ 41 ]. Pregnant rats delivered the pups normally, and that day was marked as day 0.…”
Section: Methodsmentioning
confidence: 99%